Congenital pancreatic pseudocyst presenting as neonatal ascites - M. Alzaiem; Feras Zaiem; Fadi Zaiem (Elsevier, 2016)
Congenital pancreatic pseudocysts are extremely rare in infants and very few cases have been reported in the literature. We are reporting a case of 2-month-old infant with pancreatic pseudocyst. He presented with progressive abdominal distension and large bilateral hydrocele. The diagnosis was based on the operative findings and further confirmed by histopathological examination of the wall of pseudocyst. Later on the patient was operated by laparoscopic assisted transgastric cystogastrostomy technique.